Bancassurance - Growth Guaranteed in India - Jan, Anisa; Baber, Hasnan (The Economics and Finance Letters, 2014)
The life insurance industry in India is and has been growing at a rapid rate since opening up of the sector in 2000. The size of the country, an assorted set of people pooled with problems of connectivity in rural areas, makes insurance selling in India a very difficult task. Life insurance companies require vast circulation strength and incredible human resource to come out to such a huge customer base. This delivery will undergo a sea transformation as various insurance companies are trying to bring insurance products into the lives of the common man by making them available at the most critical financial point, the local bank branch, through Bancassurance. Simply put, bancassurance is the method through which insurance products are sold to customers at their local banks.